Glycolytic reprogramming of resident alveolar macrophages contributes to reduced SOCS3 secretion in non-small cell lung cancer - Speth, Jennifer M.; Haggadone, Mikel D.; Peters-Golden, Marc (Frontiers in Immunology, 2026)
Alveolar macrophages (AMs), the resident immune cells of the lung, play a critical role in maintaining pulmonary homeostasis, in part through the secretion of suppressor of cytokine signaling 3 (SOCS3)—a recognized tumor suppressor—within extracellular vesicles (EVs). While we have previously observed that SOCS3 secretion by AMs is diminished in tumor-bearing lungs, the mechanisms underlying this impairment remain unclear. Here, we investigated whether increased glycolytic metabolism in AMs contributes to this defect within the tumor microenvironment. The analysis of published single-cell RNA-sequencing datasets from an orthotopic Lewis lung cancer (LLC) model of adenocarcinoma and non-small cell lung cancer (NSCLC) patients revealed distinct AM clusters in tumor-bearing lungs enriched for glycolysis-associated genes. In a KrasG12D mutant mouse model of lung cancer, we found that AMs isolated from tumor-bearing lungs exhibited increased glucose uptake, which inversely correlated with SOCS3 secretion. Importantly, the pharmacologic inhibition of glycolysis with 2-deoxy-d-glucose restored SOCS3 secretion in these AMs. Together, our findings demonstrate that lung tumor-associated AMs undergo a time-dependent metabolic shift toward glycolysis, resulting in impaired SOCS3 secretion—a phenotype that can be reversed by targeting glycolytic flux. These results highlight a potential therapeutic approach for modulating immune suppression in the tumor microenvironment.